Parametric study of passive air-cooled polymer electrolyte membrane fuel cell stacks. (August 2020) - Lee, Nammin; Lee, Jaeseung; Lee, Seung Woo; Jang, Seung Soon; Ju, Hyunchul
Highlights: A comprehensive parametric study was conducted using a 3D, multiscale, two-phase PEM fuel cell model to obtain a quantitative understanding of the passive air-cooled PEM fuel cell operation in excess dry air supply. This study provides comprehensive guidelines for the successful design and operation of passive air-cooled PEM fuel cell systems ABSTRACT: A passive air-cooled polymer electrolyte membrane (PEM) fuel cell stack is considered a promising technology for use in small-scale drones and unmanned aerial vehicles since it facilitates long flight durations and has a short charging time. However, in the passive air-cooling system, outside air drawn through a fan is used as both fuel for the oxygen reduction reaction and coolant for waste heat removal and using the drawn air for the two purposes is a challenging task in terms of water and heat management. A parametric study was conducted using a three-dimensional, multiscale, two-phase PEM fuel cell model to understand key water and heat transport phenomena under excess dry air supply. The effects of key design variables of the membrane electrode assembly and cathode flow-field were investigated. Furthermore, seasonal changes in the operating characteristics of air-cooled PEM fuel cell systems were analyzed. The use of a thin membrane and a high ionomer fraction in the cathode catalyst layer, and a low set-point temperature at the air outlet were found to improve the degree of electrolyte hydration and the overall cell performance. This study provides comprehensive guidelines for the successful design and operation of passive air-cooled PEM fuel cell systems.